URGENSI KONSEPSI DIRI DALAM PENGAMBILAN KEPUTUSAN KARIER - Munardji, Munardji (e-Journal STAI Muhammadiyah Tulungagung, 2014)
Career counseling is a process of assistance, information services and approach to the individual/ group of individuals to be able to know and understand themselves, to know the world of work to determine the career choice, able to take career decisions and acknowledge that the decision is the most appropriate / in accordance with the situation himself associated with requirements to be practiced career. Given the importance of career problems in human life, the children need to be prepared early on and helped to plan for a brighter future, by providing education and career guidance sustainable. Schools have an important role in career guidance. Through career counseling in elementary, junior high, high school and college facilitate learners in the achievement of his career.